Learning technology for education challenges : 7th International Workshop, LTEC 2018, Žilina, Slovakia, August 6-10, 2018, Proceedings /: 7th International Workshop, LTEC 2018, Žilina, Slovakia, August 6-10, 2018, Proceedings. (2018) - Unknown
No abstract available